Karakteristik Penyalaan Droplet Minyak Kelapa Dengan Campuran Biokatalis Karbon Aktif Kulit Pinang - Walintukan, Akbar Vicky V; Riupassa, Helen; Nanlohy, Hendry Yoshua (Rekayasa Material, Manufaktur dan Energi, 2025)
This study aims to reveal the combustion characteristics of coconut oil as an alternative fuel by adding active bio-carbon catalysts from areca nut skin. 1-3 ppm catalysts reduce viscosity, so the fuel quickly absorbs heat and ignites. This study uses the www droplet ignition method to increase the contact area between air and fuel so that the reactivity of fuel molecules increases. The results showed that adding areca nut skin-activated carbon catalysts improved fuel performance, whereas coconut oil fuel can absorb heat and release energy quickly. This was clarified from the results of the TGA test, where when compared with a mixture of 1 to 3 ppm, it was seen that the mix of coconut oil with a two ppm catalyst was the most effective because it had a high temperature with a stable heat flow. These results indicate that activated carbon from areca nut skin has excellent potential to be used as a biocatalyst for environmentally friendly and economical vegetable oil.